Membangun identitas nasional di era globalisasi: Tantangan dan strategi kebudayaan - Illa, Dimas Atok (Maliki Interdisciplinary Journal, 2025)
Globalization has significantly impacted various aspects of life, including the national identity of a nation. The widespread flow of information, the dominance of foreign cultures, and the openness of the global economy present serious challenges to preserving Indonesia’s national character. This article aims to analyze the challenges of building national identity amid the powerful currents of globalization and to formulate cultural strategies as possible solutions. Using a qualitative approach through literature review, this study finds that national identity is at risk of erosion unless supported by the reinforcement of local values, national education, and adaptive yet rooted cultural policies. Cultural strategies involving media, educational institutions, and local communities are essential in fostering collective awareness of the importance of national identity. This research concludes that building national identity is not about rejecting globalization but is a dynamic process of filtering external influences to strengthen the uniqueness and cultural sovereignty of the nation.